Acute interleukin-6 administration impairs athletic performance in healthy, trained male runners - Robson-Ansley, P. J.; de Milander, L.; Collins, M.; Noakes, T. D. (Canadian Journal of Applied Physiology, 2004)
Fatigue is an inevitable consequence of physical activity; yet its biological cause remains uncertain. During exercise, a polypeptide messenger molecule interleukin-6 (IL-6) is actively produced. Previously, the administration of recombinant IL-6 (rhIL-6) induced a heightened sensation of fatigue in healthy humans at rest. In contrast, anti-IL-6 receptor antibodies reduced the symptoms of chronic fatigue. In the present study, athletic performance during an exercise challenge consisting of a 10-km running time trial was significantly impaired in trained male runners following the administration of a low dose of rhIL-6 compared to the placebo trial.